2020
DOI: 10.1002/jpen.2005
|View full text |Cite
|
Sign up to set email alerts
|

Lessons Learned in Nutrition Therapy in Patients With Severe COVID‐19

Abstract: The coronavirus disease 2019 (COVID-19) pandemic has reached worldwide, and until a vaccine is found, it will continue to cause significant morbidity and mortality. The clinical presentation of COVID-19 ranges from that of being asymptomatic to developing a fatal illness characterized by multiple organ involvement. Approximately 20% of the patients will require hospitalization; onequarter of hospitalized patients will develop severe COVID-19 requiring admission to the intensive care unit, most frequently, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0
9

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 45 publications
(88 reference statements)
0
20
0
9
Order By: Relevance
“…Most COVID-19 patients admitted to the ICU are at high risk of or have preexisting malnutrition [ 125 ]. According to Ochoa et al, COVID-19 patients present with three different phenotypes of nutrition risk: (1) the frail older patient, (2) the patient with severe ongoing chronic illness, and (3) the patient with severe and morbid obesity [ 126 ]. The measurement of the upper waist circumference of COVID-19 patients has recently shown that with every centimeter increase there is a 1.13-fold higher probability of intensive treatment and a 1.25-fold higher probability of mechanical ventilation [ 127 ].…”
Section: Tailoring Mnt To the Individual Patient’s Needsmentioning
confidence: 99%
“…Most COVID-19 patients admitted to the ICU are at high risk of or have preexisting malnutrition [ 125 ]. According to Ochoa et al, COVID-19 patients present with three different phenotypes of nutrition risk: (1) the frail older patient, (2) the patient with severe ongoing chronic illness, and (3) the patient with severe and morbid obesity [ 126 ]. The measurement of the upper waist circumference of COVID-19 patients has recently shown that with every centimeter increase there is a 1.13-fold higher probability of intensive treatment and a 1.25-fold higher probability of mechanical ventilation [ 127 ].…”
Section: Tailoring Mnt To the Individual Patient’s Needsmentioning
confidence: 99%
“…According to Ochoa et al, COVID-19 patients present with three different phenotypes of nutrition risk: (1) The frail older patient, (2) the patient with severe ongoing chronic illness, and (3) the patient with severe and morbid obesity. [30] So far, no RCTs exist regarding nutrition in COVID-19 patients. Instead, the ESPEN and A.S.P.E.N.…”
Section: Nutrition In Critically Ill Covid-19 Patientmentioning
confidence: 99%
“…Below, we discuss the link between nutritional status and COVID-19-related aspects. As summarized in Ochoa's review, three main phenotypes have been identified as having an increased risk of severe infection: older and frail, polymorbid or with a chronic illness, and severely obese [7]. Despite the fact that most infections are asymptomatic or mild, more and more data show possible long-term consequences of the disease [8].…”
Section: Of 18mentioning
confidence: 99%